S18 Describing the triggers and sensations associated with coughing across different disease groups. (11th November 2022) - Galgani, S; Boone, L; Wingfield-Digby, J; King, J; Dockry, R; York, J; Badri, H; Smith, K; Shaw, J; Hogarth, S; Marsden, P; Smith, JA
Abstract : Introduction: Patients with Refractory Chronic Cough (RCC) frequently describe somatic sensations which trigger coughing. However, there are no current tools to quantify or aid description of these sensations and their response to antitussive therapy. The Sensations Provoking Cough (TOPIC) questionnaire quantifies the sensations and triggers of cough. Objectives: To report the pattern of cough sensations and provocations across a variety of respiratory conditions through total TOPIC score (TTS), to design a shorter novel questionnaire with potential diagnostic significance. Method: Adult patients with RCC, interstitial lung disease (ILD), asthma, chronic obstructive pulmonary disease (COPD) and bronchiectasis were recruited to complete the TOPIC questionnaire (49 items, 0–5 score range), St George's Respiratory Questionnaire (SGRQ) and Cough Severity Diary (CSD). A subset of patients completed repeat TOPIC questionnaires 5–7 days later with a Global Rating of Change to assess repeatability. Results: 167 patients (median age 62 years [range 19–88], 55.1% female) were enrolled (n=49 RCC, n=46 ILD, n=45 asthma, n=12 COPD, n=15 bronchiectasis). Patients with RCC had significantly higher median TTS than patients with ILD (106 vs 88, p=0.015) and asthma (106 vs 43, p<0.001), and a non-statistically significant higher median TTS than patients with bronchiectasis (106 vs 73, p=0.71; figure 1 ). TTS correlated with CSD across all groups (RCC R=0.539, p=0.001, ILD R=0.684, p<0.001, asthma R=0.608 p<0.001, COPD R=0.641, p=0.025, bronchiectasis R=0.597, p=0.031). TTS negatively correlated with forced vital capacity (%) in the ILD (R=-0.39, p=0.02) and bronchiectasis (R=-0.68, p=0.042) groups and forced expiratory volume (FEV1%) in the COPD group (R=-0.81, p=0.05). Intraclass correlation was significant for repeat TTS (Cronbach's Alpha=0.947, p<0.001). Conclusions: Our data suggests patients with RCC have higher levels of somatic sensations than cough associated with ILD and asthma. Higher than expected TTS in this COPD cohort was likely due to high rates of current smokers (n=7/12) and disease severity (median FEV1% 53.5 [IQR 33–59]). Differences in TTS between groups suggest that somatic sensations may vary according to pathophysiological mechanisms. The TOPIC questionnaire is highly repeatable. Further sub-analysis of TTS between groups will assist item reduction to create a novel questionnaire with potential diagnostic significance.